2011
DOI: 10.2188/jea.je20100118
|View full text |Cite
|
Sign up to set email alerts
|

Knee Pain and Future Self-Reliance in Older Adults: Evidence From a Community-Based 3-Year Cohort Study in Japan

Abstract: BackgroundAlthough knee pain is common in older persons and can cause ambulatory limitation, its impact on self-reliance has rarely been examined in Japan, particularly in a community setting. The aim of this 3-year cohort study was to investigate the association of knee pain with dependence in activities of daily living (ADL) and mortality in community-dwelling older Japanese adults.MethodsIn 2005, presence of knee pain was assessed by a home visit survey of 1391 older adults aged 65 years or older (participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…By using the WPAI-GH questionnaire, one of the few ways to understand from the patient perspective how their health is affecting their job duties, this study also provides an estimate of the economic burden of chronic pain. Compared with those without chronic pain, respondents with chronic pain were characterized by significantly greater work and activity impairment relative to those without chronic pain, which is consistent with past research in Japan that focused on work effects and impairment in activities of daily living [7][8][9]. Respondents with chronic pain reported between 73-99 % more work and activity impairment compared to those without chronic pain; this equated to approximately one-third more of work time that was missed or rendered ineffective due to health problems.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…By using the WPAI-GH questionnaire, one of the few ways to understand from the patient perspective how their health is affecting their job duties, this study also provides an estimate of the economic burden of chronic pain. Compared with those without chronic pain, respondents with chronic pain were characterized by significantly greater work and activity impairment relative to those without chronic pain, which is consistent with past research in Japan that focused on work effects and impairment in activities of daily living [7][8][9]. Respondents with chronic pain reported between 73-99 % more work and activity impairment compared to those without chronic pain; this equated to approximately one-third more of work time that was missed or rendered ineffective due to health problems.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study in Japan found a similar percentage of chronic pain patients had sought treatment (42 %), however this included both treatment through a medical institution and folk remedies and only in patients experiencing chronic musculoskeletal pain [7]. The current finding suggests an inadequacy with current treatment options which has been previously reported in prior studies in Europe [8,18].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations